(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the influence of digital media on English language comprehension among rural secondary school students in Cross River State, Nigeria, comparing those with access to digital media to those without. Utilizing a mixed-methods approach, data were collected through English comprehension tests, questionnaires, and semi-structured interviews from 300 Senior Secondary School (SSS) students across six rural schools. The sample comprised 150 students with regular digital media exposure (via smartphones and social media platforms) and 150 with minimal or no exposure. Findings reveal that students with digital media access scored significantly higher (M = 72.4, SD = 8.3) in comprehension tests compared to their counterparts (M = 58.7, SD = 9.1), with a t-value of 4.87 (p < .001). Qualitative insights indicate that digital media exposure enhances vocabulary acquisition and contextual understanding but is hindered by limited internet access and low digital literacy. The study underscores the potential of digital media to bridge educational gaps in rural settings while highlighting infrastructural challenges. Recommendations include integrating digital literacy into curricula and improving rural internet connectivity to maximize educational benefits.